Use of wearable point-of-view live streaming technology for virtual physical exam skills training - Teitelbaum, Daniel; Xie, Mary; Issa, Mariam; Nelms, Matthew; Wintraub, Lauren; Leung, Fok-Han; Nyhof-Young, Joyce; Otremba, Mirek; Sirianni, Giovanna; Prucnal, Karina (Canadian Medical Education Journal, 2022)
Implication Statement We piloted a virtual teaching tool comprised of a chest-mounted smartphone streaming point-of-view footage over videoconferencing software to deliver a physical exam skills session. Compared to medical students taught via third person view through pre-recorded video followed by preceptor-led discussion, a higher proportion of students taught via point-of-view wearable technology reported improved knowledge of demonstrated skills and feeling engaged, comfortable interacting with their tutor, and better able to visualize demonstrated exam maneuvers. This accessible, affordable, and easily replicable innovation can potentially enhance virtual clinical skills teaching and enable novel distant clinical learning opportunities for healthcare professions students and educators.